KORELASI SELF CARE TERHADAP KUALITAS HIDUP PADA PENDERITA DM TIPE 2 DI WILAYAH KERJA PUSKESMAS SARONGGI - Rohmaningsih, Ida; Mulyadi, Eko; Sumarni, Sri; Hannan, Mujib (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2024)
The increasing number of patients with type 2 diabetes mellitus poses various challenges for the elderly, including the need for self-care. This study aims to determine the relationship between self-care and quality of life among patients with type 2 diabetes mellitus in the Saringgi Health Center work area. This study used a descriptive correlational design with a cross-sectional approach and a simple purposive sampling technique. The population consisted of 123 individuals, with a sample size of 67. The instruments used were (SDSCA) to measure self-care and WHOQOL-BREF to assess quality of life. Data were analyzed using the Spearman's Rho test. The results showed that almost all respondents had a moderate level of self-care (83.6%) and good quality of life (86.6%). The Spearman's Rho test showed a result of p = 0.001 (<0.05), which indicated a significant relationship between self-care and quality of life among patients with type 2 diabetes mellitus in the Saringgi Health Center area.